(untitled) (Materiali di Estetica. Terza serie, 2020)
I have known Dino Formaggio in the year 1972. He wishes to have an assistant trained in phenomenology. I had graduated with a thesis on Edmund Husserl with Enzo Paci. I was what he was looking for. In those years he had recently published L’idea di artisticità which developed the theme of the death of art, not in a nihilistic sense but in that o the new beginning. But the theme that began to interest him was that of the expressive capacity of the body, of its originality in the construction of meaning. The second edition of the book Arte adds a beautiful analysis of Picasso’s Guernica. Dino Formaggio was also an excellent painter and sculptor: in those artistic works he offers a concrete testimony of his aesthetic thought.